Characterization and Functional Properties of Gastric Tissue-Resident Memory T Cells from Children, Adults, and the Elderly - Booth, Jayaum S.; Toapanta, Franklin R.; Salerno-Goncalves, Rosangela; Patil, Seema; Kader, Howard A.; Safta, Anca M.; Czinn, Steven J.; Greenwald, Bruce D.; Sztein, Marcelo B. (Frontiers in Immunology, 2014)
T cells are the main orchestrators of protective immunity in the stomach; however, limited information on the presence and function of the gastric T subsets is available mainly due to the difficulty in recovering high numbers of viable cells from human gastric biopsies. To overcome this shortcoming we optimized a cell isolation method that yielded high numbers of viable lamina propria mononuclear cells (LPMC) from gastric biopsies. Classic memory T (TM) subsets were identified in gastric LPMC and compared to peripheral blood mononuclear cells (PBMC) obtained from children, adults and the elderly using an optimized 14 color flow cytometry panel. A dominant effector memory (TEM) phenotype was observed in gastric LPMC CD4+ and CD8+ T cells in all age groups. We then evaluated whether these cells represented a population of gastric tissue-resident memory T (TRM) cells by assessing expression of CD103 and CD69. The vast majority of gastric LPMC CD8+ T cells either co-expressed CD103/CD69 (>70%) or expressed CD103 alone (~20%). Gastric LPMC CD4+ T cells also either co-expressed CD103/CD69 (>35%) or expressed at least one of these markers. Thus, gastric LPMC CD8+ and CD4+ T cells had the characteristics of TRM cells. Gastric CD8+ and CD4+ TRM cells produced multiple cytokines (IFN-γ, IL-2, TNF-α, IL-17A, MIP-1β) and up-regulated CD107a upon stimulation. However, marked differences were observed in their cytokine and multi-cytokine profiles when compared to their PBMC TEM counterparts. Furthermore, gastric CD8+ TRM and CD4+ TRM cells demonstrated differences in the frequency, susceptibility to activation and cytokine/multi-cytokine production profiles among the age groups. Most notably, children’s gastric TRM cells responded differently to stimuli than gastric TRM cells from adults or the elderly. In conclusion, we demonstrate the presence of gastric TRM which exhibit diverse functional characteristics in children, adults and the elderly.